2016
DOI: 10.1016/j.chembiol.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Enzymatic Formation of Bacterial Stilbene

Abstract: In contrast to stilbene biosynthesis by type III polyketide synthase in plants, in bacteria stilbene is produced by the collaboration of two enzymes in Photorhabdus luminescens: the unusual β-ketosynthase StlD catalyzes the condensation of the β-ketoacyl starter with an α,β-unsaturated-acyl substrate (two C-C bond-forming reactions) to produce isopropylstyrylcyclohexanedione, which is subsequently converted to stilbene by the aromatase StlC. Here we report the in vitro characterizations of StlD and StlC, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Evidence for a novel class of KAS, capable of catalyzing the formation of 2,5-dialkylcyclohexane-1,3-diones compounds using the same mechanism proposed for chiloglottone formation (Franke et al, 2009), have recently been reported in bacteria (Fuchs et al, 2013; Mori et al, 2016). For example, the enzyme DarB catalyzes the formation of 4-carboxy-2,5-dialkylcyclohexane-1,3-diones (Fuchs et al, 2013), via the condensation of activated β-palmitoyl with 2-butenoyl while the enzyme StlD catalyzes the formation of isopropyl styryl-2,5-dialkylcyclohexane-1,3-diones (Mori et al, 2016) using activated isovaleryl with 5-phenyl-2,4-pentadienoyl.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Evidence for a novel class of KAS, capable of catalyzing the formation of 2,5-dialkylcyclohexane-1,3-diones compounds using the same mechanism proposed for chiloglottone formation (Franke et al, 2009), have recently been reported in bacteria (Fuchs et al, 2013; Mori et al, 2016). For example, the enzyme DarB catalyzes the formation of 4-carboxy-2,5-dialkylcyclohexane-1,3-diones (Fuchs et al, 2013), via the condensation of activated β-palmitoyl with 2-butenoyl while the enzyme StlD catalyzes the formation of isopropyl styryl-2,5-dialkylcyclohexane-1,3-diones (Mori et al, 2016) using activated isovaleryl with 5-phenyl-2,4-pentadienoyl.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the enzyme DarB catalyzes the formation of 4-carboxy-2,5-dialkylcyclohexane-1,3-diones (Fuchs et al, 2013), via the condensation of activated β-palmitoyl with 2-butenoyl while the enzyme StlD catalyzes the formation of isopropyl styryl-2,5-dialkylcyclohexane-1,3-diones (Mori et al, 2016) using activated isovaleryl with 5-phenyl-2,4-pentadienoyl. Although the CtKASI paralog and bacteria DarB and StlD share low sequence similarities, further studies will be needed to ascertain whether C. trapeziformis KASI paralog have evolved additional capabilities independently to perform these condensation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…from a mangrove plant Myoporum bontioides; Wang et al 2014b), emtomopathogenic bacteria (Photorhabdus luminescens, Eleftherianos et al 2007; Bacillus sp., Kumar et al 2012), several edible mushrooms (Peng et al 2015), sponge (Antarctic sponge Kirkpatrickia variolosa, Jayatilake and Baker 1995), and moth larva (dried silkworm larva of Bombyx mori, Kikuchi et al 2004). A recent transcriptome analysis provided the evidence at the gene level that stilbenes in the endophytic fungus Alternaria could be synthesized by CHS (Che et al 2016), and a recent structural analysis revealed that the stilbene 2-isoprpyl-5-[(E)-2-phenylvinyl] benzene-1,3-diol in bacteria Photorhabdus is synthesized by the collaboration of two enzymes, the unusual b-ketosynthase StlD and the aromatase StlC (Mori et al 2016).…”
Section: Stilbene Distribution Contents and Localizationmentioning
confidence: 99%
“…In particular, the DAR motif seems to be so relevant for cyanobacterial ecophysiology that two fundamentally different biosynthetic pathways have converged to create it in the same bacterial phylum. This is remarkable since there are limited known examples of mechanistically-distinct natural product biosynthetic pathways that have converged to create the same scaffold, and even then this usually occurs in separate kingdoms 69,98,99. Despite the dissimilar biochemistry involved in creating the DAR moiety through MAR biosynthesis followed by Friedel–Crafts alkylation or by head-to-head condensation of fatty acyl precursors, a number of decorations to the DAR scaffold are installed for both pathways, including internal alkynes, glycosylation and halogenation.…”
Section: Discussionmentioning
confidence: 99%
“…By using heterologously-expressed BrtC (DarA homolog) and BrtD in a coupled assay, Leão et al 51 provided the first biochemical evidence of DarA enzymes acting as aromatases, as conversion of the fatty acyl derivative surrogates to the DAR backbone of 59–61 was observed only in the presence of BrtC. Backed by crystallographic data, Mori et al 69 showed that in bacterial stilbene biosynthesis by a DarAB system (StlC/StlD from Photorhabdus luminescens ), decarboxylation occurs during aromatization, clarifying that carboxy-CHDs are the substrates for DarA aromatases. Following DAR backbone generation, the biosynthesis of the bartolosides should proceed with the decoration of the resorcinol with sugar moieties, namely xylose and rhamnose by glycosyltransferases BrtA, E and F (diglycosylated bartolosides) or Brt A and E (monoglycosylated bartolosides), although it is unclear whether all these enzymes are involved in the glycosylations.…”
Section: Biosynthesis Of Alkylresorcinols In Cyanobacteriamentioning
confidence: 99%